Adipocyte-Cancer Cell Interactions in the Bone Microenvironment - Otley, Meredith O. C.; Sinal, Christopher J. (Frontiers in Endocrinology, 2022)
When compared to adipocytes in other anatomical sites, the interaction of bone marrow resident adipocytes with the other cells in their microenvironment is less well understood. Bone marrow adipocytes originate from a resident, self-renewing population of multipotent mesenchymal stem cells which can also give rise to other lineages such as osteoblasts. The differentiation fate of these mesenchymal progenitors can be influenced to favour adipogenesis by several factors, including the administration of thiazolidinediones and increased age. Experimental data suggests that increases in bone marrow adipose tissue volume may make bone both more attractive to metastasis and conducive to cancer cell growth. Bone marrow adipocytes are known to secrete a variety of lipids, cytokines and bioactive signaling molecules known as adipokines, which have been implicated as mediators of the interaction between adipocytes and cancer cells. Recent studies have provided new insight into the impact of bone marrow adipose tissue volume expansion in regard to supporting and exacerbating the effects of bone metastasis from prostate, breast and lung cancer. In this mini-review, recent research developments pertaining to the role of factors which increase bone marrow adipose tissue volume, as well as the role of adipocyte secreted factors, in the progression of bone metastatic prostate and breast cancer are assessed. In particular, recent findings regarding the complex cross-talk between adipocytes and metastatic cells of both lung and prostate cancer are highlighted.